Ump researchers garnered a special award and gold medal, three silver medals and six bronze medals in the inventors exhibition 2013 - Noor Syahidah, Sabran (Penerbit UMP, 2013)

(untitled)
Universiti Malaysia Pahang (UMP) made headlines again when it won a gold medal, three silver medals, six bronze medals and a special award from Korea during the International Invention Exhibition and Conference (PECIPTA 2013) held at Kuala Lumpur Convention Centre (KLCC) on November 7-9, 2013.